ANALYSIS OF PUNCTURE ACCURACY CAPABILITY IN ACEH Fencing ATHLETES BIG WEAPONS FLORET (FOIL) - Novia Rozalini; Munzir; Rivaldi Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The accuracy of thrusting in fencing is an ability evaluated by a fencer in precisely and consistently targeting the opponent. The issue faced by athletes is the precision during matches held every Sunday, and constraints on the accuracy of thrusting ability often occur. Athletes fail to hit the target accurately, thus affecting the accumulation of points. The objective of this research is to determine the accuracy of thrusting ability among fencers in Aceh Besar. This study utilizes a descriptive quantitative research approach, involving 15 participants selected through total sampling technique. Data collection is carried out through thrusting accuracy measurement tests. Data analysis involves calculating the mean values and percentages. The research findings indicate that, based on the problem statement, to assess the accuracy of thrusting ability, the average score of thrusting by fencers in Aceh Besar is 30.53, which falls into the category of very good.